2020
DOI: 10.1634/theoncologist.2019-0571
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Conveying Clinical Equipoise and Exploring Patient Treatment Preferences in an Oncology Trial Comparing Active Monitoring with Radiotherapy (ROAM/EORTC 1308)

Abstract: Introduction. Providing balanced information that emphasizes clinical equipoise (i.e., uncertainty regarding the relative merits of trial interventions) and exploring patient treatment preferences can improve informed consent and trial recruitment. Within a trial comparing adjuvant radiotherapy versus active monitoring following surgical resection for an atypical meningioma (ROAM/EORTC-1308), we explored patterns in communication and reasons why health practitioners may find it challenging to convey equipoise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Trust in the doctor and the institution is one of the most frequently cited facilitators for clinical trial participation, yet there are few interventions published that aim to address this and assess its effect on recruitment rates 26,29,33 ). The most successful to date is the Quintet Recruitment Intervention (QRI) 22,24,40,42 but this focuses mainly on the discussion between the patient and doctor rather than who the recruiter is or alliance building between the two. Further studies are recommended to address this knowledge gap.…”
Section: Discussionmentioning
confidence: 99%
“…Trust in the doctor and the institution is one of the most frequently cited facilitators for clinical trial participation, yet there are few interventions published that aim to address this and assess its effect on recruitment rates 26,29,33 ). The most successful to date is the Quintet Recruitment Intervention (QRI) 22,24,40,42 but this focuses mainly on the discussion between the patient and doctor rather than who the recruiter is or alliance building between the two. Further studies are recommended to address this knowledge gap.…”
Section: Discussionmentioning
confidence: 99%
“…A recent qualitative study addresses challenges that clinicians face when communicating that there is no good basis for a choice between two or more treatments to patients. Interestingly, the study reported that neurosurgeons not involved in the trial advised patients not to participate in the trial [ 25 ]. Another study has demonstrated a significant difference of opinion about the role of adjuvant radiotherapy after resection of WHO grade 2 meningiomas in different centers in the UK and the Republic of Ireland [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…As participants are being asked to agree to being allocated to one of two or more treatments, investigators face the task of explaining a belief in the equivalent effectiveness of these interventions-a challenging task at the best of times. 42,43 However, they must at the same time make it clear that the goal of a pilot study is not about determining the relative effectiveness of the treatments involved. Both of these considerations-the presence of equipoise and the specific purpose of the study-are likely to be relevant to a participant's decision on whether to consent, 35,38 and should therefore be communicated.…”
Section: Misperception Main Randomized Clinical Trial Pilot or Feasibility Studymentioning
confidence: 99%
“…Herein lies a particular challenge in the specific case of randomized pilot studies. As participants are being asked to agree to being allocated to one of two or more treatments, investigators face the task of explaining a belief in the equivalent effectiveness of these interventions—a challenging task at the best of times 42,43 . However, they must at the same time make it clear that the goal of a pilot study is not about determining the relative effectiveness of the treatments involved.…”
Section: Therapeutic Misperception In Pilot and Feasibility Studiesmentioning
confidence: 99%